Mahasiswa Bekerja Sambil Kuliah Sebagai Penjual Ayam Geprek - Febrianti, Cici; La Janu, La Janu; Hartini, Hartini (JURNAL KABANTI: Kerabat Antropologi, 2024)
The research aims to find out and explain the reasons why students choose to work as sellers of fried chicken, as well as to find out and explain how students plan to spend their time between went to college and worked as a fried chicken seller. The number of research informants was nine people. The dramaturgical theory developed by Erving Goffman was used in this research. This research is qualitative research that uses observation and in-depth interviews.The research results show that students choose to work as fried chicken sellers for several reasons: financial needs, filling their free time, gaining work experience, hobbies, and independent study. Meanwhile, the way students manage their time between studying and working as fried chicken sellers is by making a detailed, consistent and disciplined schedule, avoiding postponing their coursework or work, and using their rest time well.